Twitter engaged and educated dentists worldwide in dental antibiotic stewardship. - Prof Debra Goff; Dr Douglas Goff; Dr Jason Stoner; Dr Razia Adam (Elsevier, 2023)
Aim or Purpose: Determine if Twitter can engage and educate dentists in dental antibiotic stewardship.1-2 Materials and Methods: An infectious diseases-antibiotic stewardship (ID-AS) pharmacist expert with 10,000 Twitter (@idpharmd) followers posted on August 11, 2022 a visual abstract from their United States (US) study evaluating antibiotic use by private practice dentists. The tweet included a link to the study, twitter handles of selected dentists @wendythedentist, @leanne_Teoh, dental organizations @fdiworlddental @DentalCEAcademy @AmerDentalAssn @ProDentalCPD, ID-AS experts @LBaddour1 @Sudamonas @SIDPharm and C. difficile patient advocacy organization @PeggyFund. Data collected from August 11, 2022- March 31, 2023 included: number of people viewing the visual abstract tweet and ten subsequent dental antibiotic related tweets posted by @idpharmd, Twitter metrics provided by @OFIDJournal (geographic breakdown), and invited educational engagements from dentists to the ID-AS expert as a result of Twitter connections. Results: 12,494 people from 35 countries viewed the visual abstract tweet and 14,939 viewed ten subsequent dental tweets. The ID-AS expert was invited to virtually present at FDI World Dental Federation and US Dental CE Academy educating an additional 1,200 dentists from 30 and 55 countries respectively. Conclusions: Twitter provided a novel way for an ID-AS expert to engage and educate dentists worldwide in antibiotic stewardship. Dentists can use Twitter to connect with ID-AS experts to expand global collaboration in the silent pandemic of antibiotic resistance.